Le cinéma documentaire de Turquie et les fragments de la mémoire arménienne - Sibil Çekmen (Mise au Point)
This article offers an analysis of documentaries made in Turkey in the 2010s, which follows the homecoming journey of their Armenian character to the lands of their ancestors. It studies, on the one hand, the way in which they reveal the specific bond that each maintains with these lands haunted by the memory of the genocide, by focusing on the preservation and (re)construction of identity during the post-genocide period and by collecting in the respective regions the persistent fragments of individual or collective memories. It also examines how these documentaries oppose the official history of a negationist Turkey to the individual stories of (the family of) their characters, condemned to silence or oblivion. It finally discusses the possibility of reviving the collective memory through these documentaries.